Practices regarding secondhand smoking among Malay housewives in rural community in Jempol, Negeri Sembilan - Ismail, Suriani; Juni, Muhamad Hanafiah; Minhat, Halimatus Sakdiah; Mahmud, Aidalina; Muhamad Saliluddin, Suhainizam (Community Health Society Malaysia, 2015)
Introduction: Secondhand smoking occurs in public and private spaces and it causes serious adverse health effects. The initiatives to establish smoke free policies in private spaces are more challenging as it is an area of autonomy. Thus, this study aims determine the knowledge, attitude and practices of a group of housewives in a Malay community who were secondhand smokers in the privacy of their own homes and their association with these women’s socio demographic profiles.